Association between levels of exposure to heavy metals and renal function indicators of residents in environmentally vulnerable areas - Jung-Yeon Kwon; Seungho Lee; Ulziikhishig Surenbaatar; Hyoun-Ju Lim; Byoung-Gwon Kim; Sang-Yong Eom; Yong Min Cho; Woo Jin Kim; Byeng-Chul Yu; Kwan Lee; Young-Seoub Hong (Scientific Reports, 2023)
Abstract Abandoned metal mines and refineries are considered environmentally vulnerable areas owing to high levels of exposure to heavy metals. This study examined the association between heavy metal exposure and renal function indicators. We studied a total of 298 participants, of which 74 and 68 resided in low- and high-exposure abandoned metal mine areas, respectively, with 121 in the refinery area and 35 in the control area. Blood and urine samples were collected from the participants to analyze the levels of blood lead, cadmium, and creatinine and urinary cadmium, NAG, and β2-MG. The estimated glomerular filtration rate, which is calculated using the Chronic Kidney Disease Epidemiology Collaboration equation, was used for assessments. The study participants comprised more females than males, and their mean age was 70.3 years. The blood lead and cadmium as well as urinary cadmium levels were 2.12 μg/dL, 1.89 μg/L, and 2.11 μg/L, respectively, in the heavy metal-exposure areas, and 1.18 μg/dL, 0.89 μg/L, and 1.11 μg/L, respectively, in the control area. The odds ratio (OR) for exceeding the reference value showed that blood cadmium in the refinery area was 38 times higher than that in the control area. Urinary cadmium was seven times higher in the low-exposure abandoned metal mine area than in the control area. NAG showed a positive correlation with urinary cadmium in all areas. In the refinery area, correlations were observed between β2-MG and urinary cadmium levels and the eGFR and blood cadmium level; in the high-exposure abandoned metal mine area, correlations were observed between NAG, β2-MG, and the eGFR and blood cadmium. In this study, the association between Cd exposure and some renal function indicators was observed. This study’s findings and the obtained biological samples can serve as a basis for future molecular biological research.